2002
DOI: 10.1067/mva.2002.121052
|View full text |Cite
|
Sign up to set email alerts
|

High-risk carotid endarterectomy: Challenges for carotid stent protocols

Abstract: This series shows that patients at high risk can undergo carotid endarterectomy with stroke rates equivalent to the rates of patients at low risk. The cardiac morbidity rate may be increased in the high-risk group. Carotid stenting is unlikely to offer any improvement in stroke risk as compared with carotid endarterectomy, but stenting may reduce non-stroke morbidity rates associated with some high-risk cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 21 publications
3
36
0
1
Order By: Relevance
“…However, previous studies have found that the rate of new-onset atrial fibrillation is very low (<3%) after carotid revascularization. 22,23 Therefore, the atrial fibrillation diagnoses are almost exclusively based on preprocedure diagnosis. Data are lacking on the anatomic factors, including severity of carotid artery stenosis, vessel tortuosity, vascular calcifications, and status of contralateral carotid artery, that are considered high-risk features for carotid interventions and important covariates to be included in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have found that the rate of new-onset atrial fibrillation is very low (<3%) after carotid revascularization. 22,23 Therefore, the atrial fibrillation diagnoses are almost exclusively based on preprocedure diagnosis. Data are lacking on the anatomic factors, including severity of carotid artery stenosis, vessel tortuosity, vascular calcifications, and status of contralateral carotid artery, that are considered high-risk features for carotid interventions and important covariates to be included in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Because patient classification as high risk does not absolutely contraindicate CEA, we have focused on this patient subset to assess our perioperative outcome of CEA in patients classically considered high risk and compared it with those of reported series. [10][11][12][13][14][15][16][17][18][19] We hypothesized that the rate of 30-day periprocedural complications in elderly high-risk patients undergoing CEA would be no higher than that of traditional-risk patients. The purpose of this study was to determine the perioperative morbidity and mortality in patients deemed to be at high risk for complications after CEA on the basis of advanced age and antecedent comorbidities.…”
Section: See Invited Critique At End Of Articlementioning
confidence: 99%
“…Anatomic 'high-risk' features for CEA pertain to those patients with local factors that potentiate surgical morbidity, such as previous endarterectomy, prior neck external-beam irradiation, prior cervical nerve injury, contralateral internal carotid artery (increased risk of intolerance to clamping) and the presence of a potential nidus for infection (i.e., tracheostomy). The rate of cervical nerve injury may be as high as 17% in patients who have had a previous neck operation or neck irradiation, thus, CAS is an accepted indication in such cases [12,13]. In retrospective studies, CAS for restenosis following a previous endarterectomy seems to provide excellent immediate and midterm clinical outcome [14,15].…”
Section: Revascularization Endarterectomymentioning
confidence: 99%